The results of geodetic measurements of the mass balance of some glaciers in the Zailiyskiy Alatau (Trans-Ili Alatau) - A. L. Kokarev; V. P. Kapitsa; T. Bolch; I. V. Severskiy; N. Е. Kasatkin; М. Shahgedanova; Z. S. Usmanova (Лëд и снег, 2023)
SummaryThe current state and mass balance of some glaciers of the Trans-Ili Alatau (Zailiyskiy Alatau, Tien Shan, Kazakhstan) is estimated in the paper. The remote sensing data (images of the Pléiades satellites) and detailed field geodetic measurements (differential global positioning system with the South G6 instrument)were used for the analysis. The field works were carried out in August-September 2021on the northern slope of the Zailiyskiy Alatau ridge. A digital relief model had been built for the analysis as well. Negative trends in the area of the studied glaciers have been revealed, which generally correspond to the average rate of degradation of the glaciation of the Trans-Ili Alatau from 1955 to the present. A comparison of glaciological (contact, i.e., obtained as a result of measurements made on the glacier) and geodetic (resulted from analysis of remote sensing data) methods for estimating the annual mass balance of the Central Tuyuksu glacier for the period 2016-2021 showed that the final values calculated by these two methods are very close in values. For example, the sum of annual balances calculated by the glaciological method for this period was -2.9 m w.e., or -0.58 a-1 m w.e. per a year, while the balance calculated by the geodetic method for the same period was - 0.63 a-1 m w.e. Thus, the results of comparison of the above methods of the glacier mass-balance investigation confirm that the geodetic one based on satellite measurements and the ground surveys using the South G6 instrument is in a good agreement with results of glaciological methods of measurements and calculations.